COMUNICA-EB: mínimo produto viável de sistema para gestão e comunicação de escalas de trabalho da enfermagem - Fujishima, Paula Akemi (2025)
Introduction: Effective communication among healthcare professionals is one of the pillars of patient safety, being recognized by Goal 2 of the Brazilian National Patient Safety Program (PNSP) as essential for enhancing care delivery processes. The lack of structured communication flows for reporting unforeseen absences compromises continuity of care and overloads the remaining staff. In this context, Information and Communication Technologies (ICTs) have emerged as promising strategies to improve the management of nursing work schedules. Objective: To develop a Minimum Viable Product (MVP) of an application for managing and communicating nursing work schedules. Method: This is a descriptive, methodological study focused on the technological development of an MVP for the Nursing Division of the University Hospital of Sergipe. The research followed the Design Thinking (DT) approach, comprising the stages of empathy, ideation, prototyping, and development. Results: The main outcome of this project was the development of the COMUNICA-EB application, designed to support absence communication and schedule management for nursing teams. The tool enables the automated sending of notifications related to medical certificates, official declarations, and shift exchanges among staff members, optimizing the information flow and enhancing decision-making agility. The application was formally registered with the Brazilian National Institute of Industrial Property (INPI) as a Computer Program Registration, ensuring its protection as Intellectual Property (IP). In addition to the technological development, the project resulted in two scientific manuscripts and demonstrated the practical feasibility of the solution in a hospital setting. Data collected indicated that Microsoft Excel is widely used for the preparation of monthly schedules, while personal WhatsApp accounts are the primary channel for reporting unforeseen absences. This scenario reveals institutional communication weaknesses and highlights the challenges faced by managers in the daily administration of work schedules, particularly in the immediate replacement of absent professionals. The integrative literature review analyzed six articles, which indicated that technological tools applied to schedule management are based on models such as mathematical formulas, mathematical programming, participatory software, artificial intelligence algorithms, machine learning systems, and multi-agent models. The main reported benefits include balancing operational efficiency, staff satisfaction, and cost reduction, reinforcing the importance of adopting innovative solutions in health workforce management. Conclusion: COMUNICA-EB represents a technological innovation applicable to hospital environments, with potential for integration into existing systems and future incorporation of Artificial Intelligence (AI) to predict absences and support the safe staffing of nursing teams.